2020
DOI: 10.1158/1055-9965.epi-19-0963
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exclusive Use of Very Low Nicotine Cigarettes on Compensatory Smoking: An Inpatient Crossover Clinical Trial

Abstract: Background: The FDA is considering a mandated reduction in the nicotine content of cigarettes. Clinical trials have been limited by non-study cigarette use (noncompliance), which could mask compensation. The goal of this study was to assess whether compensation occurs when smokers provided with very low nicotine cigarettes cannot access normal nicotine cigarettes.Methods: In a within-subjects, crossover design, current smokers (n ¼ 16) were confined to a hotel for two 4-night hotel stays during which they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…For example, one study found that smoking declined by approximately five cigarettes per day with an accompanying decrease in carbon monoxide when non-treatment seeking participants used low nicotine cigarettes while residing on an inpatient unit for 11 days ( Donny et al., 2007 ). In another recent residential study, Smith et al. (2020) aimed to more accurately capture the effects of a real-world nicotine reduction scenario.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study found that smoking declined by approximately five cigarettes per day with an accompanying decrease in carbon monoxide when non-treatment seeking participants used low nicotine cigarettes while residing on an inpatient unit for 11 days ( Donny et al., 2007 ). In another recent residential study, Smith et al. (2020) aimed to more accurately capture the effects of a real-world nicotine reduction scenario.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, results from clinical trials consistently report reductions in smoking behavior, toxicant exposure, and nicotine dependence among adult smokers who switched to low nicotine content (LNC) cigarettes [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Such trials also report minimal evidence of the following potential unintended consequences: compensatory smoking behavior due to decreased nicotine levels, exacerbation of psychiatric symptoms, or increases in alcohol or cannabis use among adults smoking LNC cigarettes [ 12 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In a simulation study, population estimates indicate that as many as 5 million people will quit smoking within the first year of a low nicotine product standard [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be done on a per-cigarette basis or a daily-dose basis by summing results from all butts collected over a 24 h period. We have successfully used our solanesol-based approach to examine difference in deliveries and smoking behavior as a function of menthol [ 32 ], tobacco blends [ 29 , 31 ], and the use of reduced-nicotine-content cigarettes [ 34 , 35 ] for a variety of mainstream smoke constituents. However, the scanner-based method could produce comparable data while saving time and money.…”
Section: Resultsmentioning
confidence: 99%
“…Such information provides data related to smoke constituent deliveries as well as behavioral use patterns. Our laboratory successfully used this method to examine the difference in deliveries of nicotine and tobacco-specific nitrosamines [ 31 ], the influence of menthol on smoking behavior [ 32 ], differences in smoking behaviors in a clinical setting [ 33 ], and changes in smoking when cigarette nicotine content is reduced [ 34 , 35 ]. This new luminosity-based, digital-image approach is a low-cost, high-throughput method that provides comparable results to our established liquid chromatography/tandem mass spectrometry (LC/MS/MS) solanesol method [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%